Jigzoe: integrated cartoon animation studio institution in Ipoh, Perak - Shaharil, Muhammad Ihsan; Salleh, Elias @ Ilias (https://drive.google.com/file/d/19W9Ky_W9xJC_OxpCYPBjnYl_MmujP4qk/view, 2019)
Cartoon and animation are universal, effective and entertaining tools used in conveying messages. They are being used worldwide and its industry has been growing rapidly. For many years, cartoon and animation encounter many issues regarding their approaches, methods and impacts. Four main issues have been identified to affect this industry, namely stigma (social), misuse (ethical), lost identity (cultural) and downfall industry (economic).